KONTRIBUSI PEGADAIAN SYARIAH UNTUK MENUNJANG PEREKONOMIAN MASYARAKAT DI INDONESIA - RACHMAWATI, NINDA; ANANTA UPA, VIERLY (JOURNAL KOPERASI DAN MANAJEMEN, 2025)
Purpose – Pegadaian Syariah, or Islamic Pawnshops, contribute to Indonesia's economic landscape by providing accessible financial solutions aligned with Islamic principles. They offer crucial microfinancing alternatives, enabling individuals and small businesses, often excluded from traditional banking, to access capital for immediate needs and entrepreneurial endeavors. This, in turn, stimulates economic activity at the grassroots level and fosters financial inclusion within Indonesian communities. Design/methodology/approach – This study employs a qualitative approach, analyzing the contributions of Sharia pawnshops ("Pegadaian Syariah") in supporting the Indonesian economy. The research methodology focuses on examining the operational models, financing schemes, and social impact of Pegadaian Syariah on local communities and micro-enterprises, drawing upon existing literature, reports, and case studies to understand its role in fostering financial inclusion and economic empowerment. Findings – The research indicates that Pegadaian Syariah (Islamic Pawnshops) significantly contributes to supporting the Indonesian economy, particularly for communities requiring short-term financing. This contribution manifests through accessible financial services, fostering entrepreneurship, and providing a viable alternative to informal lending practices, ultimately promoting financial inclusion and economic stability. Research limitations/implications – This study's limitations include its specific focus on Pegadaian Syariah's impact within Indonesia, potentially limiting the generalizability of findings to other contexts or Islamic microfinance institutions. Future research should explore a broader range of institutions and economic development indicators to provide a more comprehensive understanding of the contribution of Islamic pawnshops to societal well-being and economic growth. The findings, however, offer valuable insights for policymakers and practitioners seeking to optimize the role of Pegadaian Syariah in supporting financial inclusion and economic empowerment within the Indonesian context. Originality/value – Pegadaian Syariah, or Islamic pawnshops, contribute to Indonesia's economy by providing accessible financing solutions, particularly for micro, small, and medium enterprises (MSMEs) and underserved communities. These institutions offer Sharia-compliant financial services that promote economic inclusion and empower individuals to access capital without resorting to conventional interest-based lending, fostering a more equitable and sustainable financial ecosystem.